2019
DOI: 10.5093/ejpalc2019a3
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Traffic Offenders: Alcohol Consumption and Personality as Predictors of Driving Disqualification

Abstract: Traffic safety is an important social problem. Many accidents are due to non-compliance with traffic regulations. Serious or repeated offenses are sanctioned with penalty points or court conviction, and sanctions can lead to disqualification from driving. This paper explores the relevance of alcohol consumption and personality factors as predictors of driving disqualification. The aim of the study is to determine whether the behaviors of persistent offenders and their propensity for law-breaking are related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 38 publications
(44 reference statements)
0
28
0
5
Order By: Relevance
“…First of all, in the present study young cyclists presented a major latent risk, based on both their behavioral patterns and their self-reported cycling crashes suffered during the past few years ( M = .89). In accordance, similar researches have described how age decreases behavioral risks among cyclists [39]; also, other studies involving other types of road users, especially motor-vehicle drivers, have found hazardous trends in terms of risky road behaviors [40–42], low risk perception [43,44] and a scarce knowledge of traffic norms [45–47] among young people, especially those under 25. In this regard, most studies dealing with young drivers have remarked that young road users constitute a crucial focus to address in road safety interventions [48].…”
Section: Resultsmentioning
confidence: 64%
“…First of all, in the present study young cyclists presented a major latent risk, based on both their behavioral patterns and their self-reported cycling crashes suffered during the past few years ( M = .89). In accordance, similar researches have described how age decreases behavioral risks among cyclists [39]; also, other studies involving other types of road users, especially motor-vehicle drivers, have found hazardous trends in terms of risky road behaviors [40–42], low risk perception [43,44] and a scarce knowledge of traffic norms [45–47] among young people, especially those under 25. In this regard, most studies dealing with young drivers have remarked that young road users constitute a crucial focus to address in road safety interventions [48].…”
Section: Resultsmentioning
confidence: 64%
“…Regarding the existing evidence in the working population, EEW has already been related to different adverse health consequences such as: depressive and anxious disorders [26,27], systematic headaches [28], a greater Odds Ratio (OR) for developing hypertension [29] gastrointestinal diseases [30], musculoskeletal disorders [28], acute/chronic fatigue [31,32], numerous sleep problems [33][34][35], and a lower performance at work, in comparison to workforce groups that, on the other hand, have not reported burnout symptoms [36,37]. Empirically, some studies have found that burnout-related issues, such as EEW, may explain higher rates of job absenteeism and consistent turnover rates of workers [6,38,39], including the case of professional drivers, whose stressful work environment and role conflicts seem to be closely related to the appearance and prevalence of burnout-related symptomatology and other negative occupational and health outcomes [40,41].…”
Section: Associations Between Emotional Exhaustion At Work Health Anmentioning
confidence: 99%
“…Nevertheless, it is relatively common to see how many drivers undervalue the impact of such factors on driving safety [5]. In this sense, the understanding of many health-related factors which affect the driving performance and the increase of the knowledge and awareness of drivers implies that relevant actions that can be taken, since they are tools which may strengthen road safety [6,7]. This is especially relevant when considering certain facts, such as that the prevalence of mental disorders is considerably frequent-and approximately a third of people will suffer from these disorders at some point of their lives- [8].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, researchers verified alcohol consumption and personality factors as predictors of risk driving in offending drivers compared to non-offenders. The results showed that increased factors such as sensation seeking were associated with hostility while driving [25].…”
Section: Introductionmentioning
confidence: 99%